(untitled) (Belgium, 1980)
The brine shrimp Artemia is a small aquatic invertebrate which is used worldwide as a live food in aquaculture. Unlike most other marine organisms, it is an ideal species for toxicity tests because: (i) it does not require the maintenance of stock cultures; (ii) it can be cultivated in massive numbers in a limited amount of water; (iii) it has a very short life-span, enabling many experiments to be conducted in a short time; (iv) as it is transparent, microscopic examinations of live specimen are possible; and (v) its abundance facilitates replication for statistical analyses.
Keywords: Artemia,Crustacea,Microbiology